Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes - Laurent, Ryan A. St; Cock, Matthew J. W. (Zootaxa, 2017)
We present the first list focused on Mimallonidae from Trinidad and Tobago and report seven genera and 13 species from Trinidad, and two genera and two species from Tobago, one species of which has not yet been found in Trinidad. All species found on these islands are figured, with the exception of the species known only from Tobago. Additionally, we describe a new species: Cicinnus trini, sp. n. This new species is closely allied to C. beta (Schaus, 1910), comb. n. and C. veigli (Schaus, 1934), comb. n. which we transfer to Cicinnus Blanchard, 1852 from Psychocampa Grote & Robinson, 1866 based on male genitalia characteristics. We designate lectotypes for C. beta, C. magnapuncta (Kaye, 1901), and Trogoptera guianaca Schaus, 1928.